Konstruksi Teologi dalam Konteks Reposisi Pemikiran Warga Gereja - Kevin Tonny Rey (Sekolah Tinggi Teologi Torsina Surakarta, 2018)
Theology is an effort which people does in order to have an understanding about God of whom worshipped to be, thus what church did. Theology must have a construction that resulted in an understanding for congregations according to their limitations. This article aimed to give this congregation about the meaning of theology itself so that not to be entrapped in the theological issues those erasing the obvious concept about God. The methodology used in this article is a philosophical analysis about the meaning of theology itself for a congregation. The conclusion is that theology must be viewed at several sides, which are: its relation with history, dialogue, and context so that theology is understandable in the context of developing culture.AbstrakTeologi merupakan usaha manusia untuk mengerti tentang Allah yang disembahnya, demikian pula oleh warga gereja. Teologi harus memiliki konstruksi yang menghasilkan pemahaman bagi warga gereja sesuai dengan keterbatasan mereka. Artikel bertujuan untuk memberikan pemahaman tentang makna teologi bagi warga gereja agar tidak terjebak pada persoalan-persoalan teologi yang menghilangkan konsep Allah yang jelas. Metode yang digunakan adalah analisis filosofis mengenai makna teologi bagi warga gereja. Kesimpulannya, teologi harus dipandang pada beberapa sisi, yakni dalam relasinya dengan sejarah, dialogis dan relasi konteks, sehingga teologi mampu dipahami dalam konteks budaya yang terus berkembang.